Unexplained fever and rash: a case of Schnitzler syndrome - Yali Wu; Yuan Wang; Baoyu Zhang (The Egyptian Journal of Internal Medicine)
Abstract Introduction Fever, rash and joint pain are common manifestations of rheumatism. The article reports a patient with recurrent fever and rash, and the final diagnosis of Schnitzler syndrome. The course of diagnosis and treatment was described in detail, and the clinical manifestations, pathogenesis, diagnosis and treatment of the disease were further discussed. Case presentation In this article, we report a 59-year-old man who had recurrent fever, rash, and joint pain for 7 years. Once considered as adult still's disease, anti-neutrophil cytoplasmic antibody-associated vasculitis and systemic inflammatory response syndrome, long term use of hormones and immunosuppressants for treatment, with intermittent attacks, about 15–20 days per occurrence. The interval of rash and fever in the two weeks before admission has shortened, about every 3–5 days. No abnormalities were found in infection, immunity and other related examinations, IgM κ M protein was positive, PET-CT and bone marrow biopsy did not indicate tumor, the patient met the diagnostic criteria for Strasbourg Schnitzler syndrome, and Schnitzler syndrome was finally diagnosed. Result The patient was treated with tocilizumab, a humanized anti-IL-6 receptor antibody, and developed skin allergy. Adjustment for methylprednisolone 8 mg once a day, colchicine 0.5 mg twice a day, tofacitinib 5 mg twice a day, waiting for IL-1 receptor antagonist.